Research Data Management 1 Day Workshop - El-Gebali, Sara (My University, 2021)
Materials for 1 full-day workshop on Research Data Management basics covering the following topics: Part 1: Overview of the RDM unit services and support Part 2: What is Data? Part 3: FAIR data Part 4: Open Data Part 5: Reuse and Reproducibility Part 6:Where do we start? Part 7: Documentation - Electronic lab notebooks - Metadata - README files Examples of breakout room exercises and discussion questions included. - For feedback please feel free to get in touch by email or Twitter Resources: Research data management: Making the Case for Research Data Management https://www.dcc.ac.uk/guidance/briefing-papers/making-case-rdm What is Research Data? https://www2.le.ac.uk/services/research-data/old-2019-12-11/documents/UoL_ReserchDataDefinitions_20120904.pdf New England Collaborative Data Management Curriculum https://library.umassmed.edu/resources/necdmc/modules Science Europe- RDM guide: https://scienceeurope.org/our-resources/practical-guide-to-the-international-alignment-of-research-data-management/ Roberts Lab Handbook- Data management in life sciences https://robertslab.github.io/resources/Data-Management/ Research data management (RDM) open training materials https://zenodo.org/communities/dcc-rdm-training-materials/?page=1&size=20
What is data & FAIR data: Research Libraries’ https://www.liberquarterly.eu/article/10.18352/lq.9173/ Zenodo-FAIR principles: https://about.zenodo.org/principles/ "A love letter to your future self": What scientists need to know about FAIR data https://www.natureindex.com/news-blog/what-scientists-need-to-know-about-fair-data Invest 5% of research funds in ensuring data are reusable https://www.nature.com/articles/d41586-020-00505-7 FAIRaware- FAIR assessment https://fairaware.dans.knaw.nl/ H2020 Programme Guidelines on FAIR Data Management in Horizon 2020 https://ec.europa.eu/research/participants/data/ref/h2020/grants_manual/hi/oa_pilot/h2020-hi-oa-data-mgt_en.pdf FAIRsFAIR Europe https://www.fairsfair.eu/ How to FAIR https://howtofair.dk/ Go FAIR https://www.go-fair.org/ FAIR sharing https://fairsharing.org/ Open Data & reuse, reproducibility: Mozilla open science- challenges to open data and how to respond: https://github.com/mozillascience/open-data-training/blob/master/Materials/Handouts/ODChallengesQI.md Ten arguments against Open Science that you can win: https://www.software.ac.uk/blog/2020-12-17-ten-arguments-against-open-science-you-can-win ‘I ain’t afraid of no myth’ – busting the myths on data sharing: https://blog.wellcomeopenresearch.org/2020/08/20/i-aint-afraid-of-no-myth-busting-the-myths-on-data-sharing/ OpenAIRE Research Data Management Hand Book https://www.openaire.eu/rdm-handbook Open Data Hand Book https://opendatahandbook.org/guide/en/why-open-data/ Open Science Hand Book https://zenodo.org/record/1212496 Papers Without Code - submission https://www.paperswithoutcode.com/ Open Data and FAIR Data: differences and similarities https://www.ogoov.com/en/blog/open-data-and-fair-data-differences-and-similarities/ Open Science Mooc: https://opensciencemooc.eu/ Rein in the four horsemen of irreproducibility https://www.nature.com/articles/d41586-019-01307-2 Making experimental data tables in the life sciences more FAIR: a pragmatic approach https://academic.oup.com/gigascience/article/9/12/giaa144/6034785 Open Scientist Handbook https://openscientist.pubpub.org/ German reproducibility network https://reproducibilitynetwork.de/ The Turing Way https://the-turing-way.netlify.app/welcome Data Organization: Towards a Standardized Research Folder Structure https://genr.eu/wp/towards-a-standardized-research-folder-structure/ Swedish National Data service https://snd.gu.se/en/manage-data/guides/suggested-file-formats DataOne research data management modules: https://old.dataone.org/education-modules Imperial College Research data management guides: https://www.imperial.ac.uk/research-and-innovation/support-for-staff/scholarly-communication/research-data-management/introduction-to-research-data-management/ King’s college- Managing your data: https://www.kcl.ac.uk/researchsupport/managing UK Data Services: https://www.ukdataservice.ac.uk/manage-data.aspx Electronic Lab notebooks: Cambridge University Guide https://www.data.cam.ac.uk/data-management-guide/electronic-research-notebooks/electronic-research-notebook-products LabFolder white papers on Compliance https://www.labfolder.com/white-papers/ Electronic Code of Federal Regulations-CFR https://www.ecfr.gov/cgi-bin/text-idx?SID=140a04c31974ef0891cfb2555bc3a865&mc=true&node=pt21.1.11&rgn=div5 Cost-benefit analysis for FAIR research data https://op.europa.eu/en/publication-detail/-/publication/d3766478-1a09-11e9-8d04-01aa75ed71a1/language-en Invest 5% of research funds in ensuring data are reusable article https://www.nature.com/articles/d41586-020-00505-7 Harvard Matrix https://shrtco.de/G55Dy University of Glasgow Adapted Matrix https://docs.google.com/spreadsheets/d/1egUW3ZewyIaJ_lhEe8uJrd-69ycVbqQjiqbJxbs_jVY/edit#gid=1172088166 Research Notebooks Blog https://researchnotebooks.wordpress.com/outputs/ Metadata: Repository finder: https://repositoryfinder.datacite.org/ Dublin Core Metadata initiative https://www.dublincore.org/resources/metadata-basics/ Documentation and Metadata-Stockholm university: https://pp-prod-admin.it.su.se/preview/www/2.153/2.213/2.30381/2.38402/2.49278/2.53084#Documentation%20and%20metadata ANDs guide-Metadata: https://www.ands.org.au/__data/assets/pdf_file/0004/728041/Metadata-Workinglevel.pdf RD-alliance repositories: http://rd-alliance.github.io/metadata-directory/standards/ Cessda-Documentation & Metadata: https://www.cessda.eu/Training/Training-Resources/Library/Data-Management-Expert-Guide/2.-Organise-Document/Documentation-and-metadata What is Metadata? 5-min video tutorial https://vimeo.com/3161893 JISC Metadata guide: https://www.jisc.ac.uk/full-guide/metadata FAIRsharing as a community approach to standards, repositories and policies https://www.nature.com/articles/s41587-019-0080-8 Digital Curation Center: https://www.dcc.ac.uk/guidance/standards/metadata Guidelines for writing“readme” stylemetadata https://data.research.cornell.edu/sites/default/files/SciMD_ReadMe_Guidelines_v4_1_0.pdf Software: Reproducible analysis and Research Transparency https://reproducible-analysis-workshop.readthedocs.io/en/latest/ Data Science for the Biomedical Sciences https://ds4biomed.tech/
Keywords: FAIR; Open data; Research data management